Dual Education – A New Stage in Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
At all stages of human society, the development of society and the state has been closely linked to the field of education. Education and upbringing play a key role in the family, which is considered the fundamental unit of society, particularly in raising children. Upbringing is a systematized process aimed at the comprehensive development of the younger generation, forming their consciousness, moral-spiritual values, and worldview based on clear goals and socio-historical experience. Education, in turn, is a systematized process aimed at providing learners with deep theoretical knowledge, skills, and practical competencies, as well as shaping their general and professional knowledge, skills, and abilities, and developing their potential.